Prevalence and Related Factors of Dizziness Among Older Adults: A Cross-Sectional Study in Ardakan City, Iran - Morowatisharifabad, Mohammad A.; Sharifabad, Mahdieh Hosseini; Aboutorabi-zarchi, Marzieh (Current Aging Science, 2024)
Background: Dizziness and balance disorders are directly related to aging in humans- Dizziness is one of the most important factors causing the burden of disability after the age of 65. Bearing in mind the increase in the elderly population in Iran and the world and the prevalence of dizziness in old age, early diagnosis of dizziness and determination of the factors affecting its severity facilitate its treatment and are effective in preventing its adverse consequences. Objective: To determine the prevalence of dizziness and its related factors among older adults in Ardakan city, Yazd province, Iran, in 2022. Methods: This cross-sectional study was conducted in four comprehensive health centers of Ardakan city with the participation of 260 elderly people aged ≥60 years, who were randomly included in the study. Data were collected using a series of questionnaires which were completed by interviewing the participants. The variables of this study included demographic information, information related to the dizziness status, diseases, medications, use of mobility aids, physical activity level, fear of falling, quality of life and depression. Results: The prevalence of dizziness among older adults of Ardakan city was 48.5%. In terms of the severity of dizziness, 38.8% had substantial dizziness, and 9.6% had mild dizziness. Dizziness was significantly related to physical activity (p<0.05), fear of falling (p <0.01), depression (p <0.05), history of falling (p <0.01), use of mobility aids (p <0.01), age (p<0.01), education level (p<0.01), gender (p <0.05) and diseases such as high blood pressure (p<0.05), hypothyroidism (p <0.01) and ear diseases(p <0.01). Also, elderly people with dizziness used significantly more medications such as sedatives (p<0.01), antihypertensive drugs (p <0.05) and cytotoxic drugs (p <0.01). Conclusion: About half of the older adults experience dizziness, and this problem is associated with depression, fear of falling, history of falling, low physical activity, age, female gender, ear diseases, high blood pressure, and hypothyroidism. In addition, the use of medications such as anti- hypertensives, sedatives and cytotoxic drugs is related to dizziness. Families with elderly people, doctors and healthcare workers need to be educated and pay more attention to the above.
Keywords: risk factors